2018
DOI: 10.1007/s12088-018-0715-3
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Products of Carbamazepine (CBZ) After Ozonation and their Toxicity Evaluation Using Pseudomonas sp. Strain KSH-1 in Aqueous Matrices

Abstract: Carbamazepine (CBZ) is an anti-epileptic and anti-convulsant drug widely used for the treatment of epilepsy and other bipolar disorders. Ozone as an advanced oxidation process has been widely used for the degradation of CBZ resulting in the formation of transformation products (ozonides). The present research aims to isolate and identify potential microorganism, capable of degradation of CBZ and its transformation products. The cell viability and cytotoxicity of pure CBZ and their ozone transformation products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Catalysts 2020, 10, 90 13 of 20 25.7 mg/L but after 2 h it decreased to 4.8 mg/L. Pt-H-Y-12-EIM and Ru-MCM-41-IS catalysts showed a slightly higher transformation rate of BQM compared to the corresponding non-catalytic experiment.…”
Section: Quantification Of Catalytic and Non-catalytic Ozonation Prodmentioning
confidence: 85%
See 1 more Smart Citation
“…Catalysts 2020, 10, 90 13 of 20 25.7 mg/L but after 2 h it decreased to 4.8 mg/L. Pt-H-Y-12-EIM and Ru-MCM-41-IS catalysts showed a slightly higher transformation rate of BQM compared to the corresponding non-catalytic experiment.…”
Section: Quantification Of Catalytic and Non-catalytic Ozonation Prodmentioning
confidence: 85%
“…Ozonation of CBZ gives some resistant by-products due to the ozone reaction by the olefin group in CBZ, producing an ozonide, which divides the double bond [24]. The major identified by-products from ozonation of CBZ were BQM and BQD [25]. Some methods have been proposed to improve the ozonation of CBZ due to reducing the by-product such as combination by soil aquifer treatment column that enhances degradation of BQD yet the other by-products were more resistance up to 5-6 days [26].…”
Section: Introductionmentioning
confidence: 99%
“…Novel technologies with the aim to improve STP removal efficiencies of pharmaceuticals and other micropollutants are being investigated . Studies on ozonation as a tertiary STP effluent treatment technology have shown that CBZ can be removed by more than 90%. However, ozonation of CBZ can cause increased toxicity as observed in zebrafish (Danio rerio) embryos, and cell-based in vitro assays. , Because the CBZ molecule has a high degree of reactivity with ozone, several intermediaries, that is, ozonation byproducts (OBPs), are created. Two key OBPs, 1-(2-benzaldehyde)-4-hydro-(1 H ,3 H )-quinazoline-2-one (BQM) and 1-(2-benzaldehyde)-(1 H ,3 H )-quinazoline-2,4-dione (BQD), have been identified previously. Besides, 10,11-Dihydrocarbamazepine (DI-CBZ) and the therapeutically active CBZ metabolite CBZ-EP have been quantified after ozonation of CBZ …”
Section: Introductionmentioning
confidence: 99%
“…21−23 can cause increased toxicity as observed in zebrafish (Danio rerio) embryos, 17 and cell-based in vitro assays. 24,25 Because the CBZ molecule has a high degree of reactivity with ozone, several intermediaries, that is, ozonation byproducts (OBPs), are created. Two key OBPs, 1-(2-benzaldehyde)-4-hydro-(1H,3H)-quinazoline-2-one (BQM) and 1-(2-benzaldehyde)-(1H,3H)-quinazoline-2,4-dione (BQD), have been identified previously.…”
Section: Introductionmentioning
confidence: 99%